Assessment of the quality of life of children having the treatment for congenital hip dislocation - V. V. Kozhevnikov; Е. V. Voronchikhin; А. А. Nechaeva; I. А. Kirilova; А. А. Korytkin (Сибирский научный медицинский журнал)
Long-term surgical treatment outcomes in children with congenital hip dislocation can be various and depend on many factors, including the age in time of surgery. The quality of life assessment systems are modern tools to study the effectiveness of previous treatment, as well as to plan subsequent comprehensive rehabilitation. Material and methods. The study included 68 children divided into the groups according to the age of the primary surgical intervention. There were three groups: group 1 – 21 patients under 1.5 years, group 2 – 22 children aged 1.5–4-years, group 3 – 25 children over 4 years. Objective medical assessment of the clinical outcomes was carried out with the McKay’s criteria. The PedsQL4.0 questionnaire, pediatric and parental forms were used to assess the patients’ quality of life. Results. The majority of children in the 1st age group had excellent results (52.3%), in the 2nd and 3rd groups there were fewer such results (40.9 and 32 %, respectively). Having analyzed the data of the questionnaires for children and their caregivers we found that the both categories from group 3 demonstrated the lowest quality of life parameters. Conclusions. The frequency of consequences such as discomfort, limping, limb length discrepancy was also higher in children underwent surgery at the age of over 4 years old. It correlates with the questionnaire results and demonstrates a lower quality of life in children from group 3.